Safety and efficacy of fentanyl versus pethidine in cataract surgery under propofol- based sedation: A double-blind randomized controlled clinical trial - Hamidreza Shetabi; Seyed Jalal Hashemi; Fariba Haghi; Dariush Moradi Farsani (Journal of Research in Medical Sciences, 2020)
Background: The study was aimed to evaluate the safety and efficacy of fentanyl and pethidine on the sedative quality of patients who underwent phacoemulsification cataract surgery with Propofol. Materials and Methods: In this double-blind randomized controlled clinical trial, patients who were candidates for elective phacoemulsification surgery with topical anesthesia were enrolled. The selected patients were randomly allocated into the two groups for receiving sedation with Propofol-Pethidine (PP) or propofol-fentanyl (PF) combinations. Demographic characteristics, hemodynamic parameters before, during, and after the operation, sedation and pain scores, and patients' and surgeons' satisfaction scores were compared in the two studied groups. Results: In this trial, 70 patients (35 patients in each group) have completed the study. Mean (standard deviation) operation time was 22.9 (6.8) and 25.46 (7.7) minutes in PF and PP groups (P = 0.118).Mean pain score in PF 0.46 (0.14) was significantly higher than PP groups 0.236 (0.06) (P = 0.011). The mean value of diastolic and systolic blood pressures, pulse rate, and mean arterial pressure dioxide were significantly decreased in both PF and PP groups (PTime< 0.001), although there was no significant difference between groups. Conclusion: Our findings indicated the equivalence effects on hemodynamic parameters for both pethidine and fentanyl in combination with propofol in which they could provide appropriate sedation and safe anesthesia with lower complications and acceptable patients' and surgeons' satisfaction.